2021
DOI: 10.3390/jmse10010017
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Flooded Compartment Damage Locations in Ships by Using Spectrum Analysis of Ship Motions in Waves

Abstract: Considering the nature of marine accidents, even a single accident can result in significant damage to the environment and property, as well as loss of life. Therefore, the initial response should be rapid and accurate, and various decision support systems have been developed to achieve this. Research on simulating progressive flooding on board immediately after an accident is being actively conducted, but this requires high levels of computing power. In this study, a methodology for converting simulated ship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Other studies have introduced hybrid or multi-level real-time flooding risk evaluation [124]. Furthermore, recent studies have shown the potential for the application of data-driven techniques to the problem based on pre-calculated progressive flooding simulations [125][126][127][128][129].…”
Section: Predictionmentioning
confidence: 99%
“…Other studies have introduced hybrid or multi-level real-time flooding risk evaluation [124]. Furthermore, recent studies have shown the potential for the application of data-driven techniques to the problem based on pre-calculated progressive flooding simulations [125][126][127][128][129].…”
Section: Predictionmentioning
confidence: 99%
“…It can be used for decision-making in case of progressive flooding simulation or accident response by predicting the location of damage with high accuracy without using flood sensors or direct searching by a crew member. In the prior study (Son et al, 2021), an algorithm for predicting the location of damage was developed using the short time Fourier transform (STFT) to obtain the case most similar to the real-time ship motion data among the damaged ship simulation data in various scenarios. Time-series data was transformed to a spectrogram matrix using STFT, and the real-time motion data converted under the same conditions were compared with all simulated scenarios to predict the damage location.…”
mentioning
confidence: 99%